Explaining the gender gap in profits among entrepreneurs in Malawi - Duval-Diop, Dominique; Heckert, Jessica; Lee, Jean; Seymour, Greg; Vaughn, Katherine (International Food Policy Research Institute, 2021)
In this paper, we utilize decomposition methods to document the extent and drivers of the performance gap in Malawi between firms with a female owner and firms with a male owner. We find that, on average, male-owned businesses in Malawi earn profits more than double (120%) those of female-owned businesses. We use Kitagawa-Oaxaca-Blinder (KOB) mean-decomposition techniques and recentered influence function (RIF) regressions applied along the earnings distribution, coupled with data from a novel multi-topic household survey rich in details about entrepreneurship, to identify what proportion of the gender gap in business profits can be attributed to: (i) differences in average characteristics of profit-generating factors (composition effect) and (ii) gender differences in the returns to these factors (structure effect). We find that 59.8% of the mean gender gap is explained by gender differences in the levels of observable attributes, with the remaining 40.2% attributable to the lower returns to observable attributes obtained by female owners, i.e., female structural disadvantage. The composition effect is primarily driven by female owners’ role as the primary caregiver in most households and a lack of capital. The female structural disadvantage can largely be attributed to female owners’ heightened perception of sexual hostility in the work environment and non-cognitive skills related to entrepreneurship (perseverance in challenging tasks and environments, optimism, and passion for work). When looking along the distribution, capital stock appears to be a primary driver of the composition effect except in the bottom quintile of firms. In contrast, caregiving responsibilities are a driver of the composition effect in the bottom three quintiles only. Differences in the returns to capital appear to be a very significant driver of the female structural disadvantage in the bottom quintile.